CHARACTERISTIC DISTINGUISHMENTS OF PANCA MAHA BHUTA AS A BALINESE CULTURAL HEALTH SERVICE AT THE FIVELEMENTS RETREAT BALI HOTEL - Gede Yoga Kharisma Pradana; I Putu Sabda Jayendra (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The purpose of this article is to reveal the distinctive characteristics of Panca Maha Bhuta at Fivelements Retreat Hotel Bali. Panca Maha Bhuta is a local wisdom in Balinese culture that is often practiced by Balinese people in Hindu ritual activities. However, there is a Panca Maha Bhuta service intended for guests of Fivelements Retreat Hotel Bali. The problem formulation centers on: 1) What is the form of Panca Maha Bhuta at Fivelements Retreat Hotel Bali?; 2) Is there a nexus of Balinese cultural elements in Panca Maha Bhuta at Fivelements Retreat Hotel Bali?; 3) What is the distinctive form of Panca Maha Bhuta characteristics at Fivelements Retreat Hotel Bali?. This study uses a qualitative method. Observations and interviews with informants at Fivelements Retreat Hotel Bali have been conducted to collect primary data. Literature studies have been useful in searching for secondary data. The totality of data was analyzed qualitatively using the theory of power relations of knowledge and symbol theory. The results of the research are: 1) Panca Maha Bhuta is a special type of health service for guests of the Fivelements Retreat Bali Hotel; 2) There is a nexus of Balinese cultural elements in Panca Maha Bhuta at the Fivelements Retreat Bali Hotel; 3) The distinctive characteristics of Panca Maha Bhuta at the Fivelements Retreat Bali Hotel lie in the representation of Balinese culture in the name of the service package, the Balinese cultural style in the service package protocol components and the operational sensation.